Peningkatan Kemampuan Literasi Baca Siswa Melalui Penerapan Problem Based Learning Di Kelas V SD Negeri 010 Talontam - Vista Cindy; Dariasmiati Lasda (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to increase students' reading literacy through the application of the problem based learning model in class V of SD Negeri 010 Talontam for the 2022/2023 academic year. This research is classroom action research which was carried out in 2 cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were 23 fifth grade students at SD Negeri 010 Talontam for the 2022/2023 academic year. Research data was obtained through tests. The increase in Reading Literacy is shown by the increase in the average percentage of students' reading literacy which increased from 46.52% in the pre-cycle to 56.52% in the first cycle, and then to 76.52% in the second cycle. This shows an increase in reading literacy. Based on these findings, it can be concluded that the problem based learning method used in class V of SD Negeri 010 Talontam for the 2022/2023 academic year has improved students' reading literacy skills.